2013
DOI: 10.1177/1029864912467632
|View full text |Cite
|
Sign up to set email alerts
|

Inferring musical structure through bodily gestures

Abstract: Despite the idiosyncrasies present in bodily motion during musical performances, it is suggested that these movements are not incidental but instead contribute to the meaning of performed music. Nine pianists performing two Chopin Preludes are recorded using Vicon motion capture, in synchrony with audio and MIDI recordings. Using principal components analysis (PCA) on the recorded upper body motion, motion profiles for each pianist are formed from the weighted combinations of these components. This measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
9
39
0
3
Order By: Relevance
“…Previous investigations sought to examine the generation of repetitive motion over phrases of similar rhythmic duration and complexity by comparing the two-bar phrasing structure of the A major Prelude, and similar instances arising in the B minor Prelude, in order to investigate consistency of performance gesture over similar phrases within multiple performances of differing compositions (MacRitchie et al, 2013). Those findings are extended here to consider the more varied phrasing structure of the B minor Prelude in its entirety.…”
Section: Methods and Designmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous investigations sought to examine the generation of repetitive motion over phrases of similar rhythmic duration and complexity by comparing the two-bar phrasing structure of the A major Prelude, and similar instances arising in the B minor Prelude, in order to investigate consistency of performance gesture over similar phrases within multiple performances of differing compositions (MacRitchie et al, 2013). Those findings are extended here to consider the more varied phrasing structure of the B minor Prelude in its entirety.…”
Section: Methods and Designmentioning
confidence: 98%
“…The authors have previously identified motion patterns as recurrent and idiosyncratic within nine highly skilled performers' individual motion profiles, generated through principal component analysis (PCA) of overall upper-body and head performance motions (MacRitchie, Buck & Bailey, 2013). A motion profile, as defined in this previous paper, is a weighted combination of the first few principal components such that the total variance explained is above 90%.…”
Section: Identification Of Performance Gesturementioning
confidence: 99%
See 1 more Smart Citation
“…The former approach is problematic because of the limited validity of ''faked'' expressive movements, and the latter because the movements and gestures in musical performance have been found to arise from a representation of the musical structure, and thus convey meaning in association with specific musical passages (e.g., MacRitchie, Buck, & Bailey, 2013).…”
Section: Usic Is An Inherently Multisensorymentioning
confidence: 99%
“…Pour cette raison, plusieurs études se servent de techniques comme l'analyse en composantes principales (PCA) pour décomposer le mouvement en éléments de base localisés (eigenmovements), et estimer leur synchronisation aux unités métriques de la partition. On en trouve un exemple chez [MacRitchie 2009] qui identifie les mouvements de la tête et du haut du buste des pianistes comme des composantes essentielles pour la structure du phrasé. Mais c'est surtout dans le domaine de la danse spontanée en réaction à la musique que s'applique ce type d'analyse du mouvement d'ensemble [Amelynck 2014].…”
Section: Décodage Rythmique Ancillaireunclassified